Alih Fungsi Ekosistem Hutan Manggrove di Kabupaten Aceh Tamiang - Muazzin Muazzin; Enzus Tinianus (Kanun Jurnal Ilmu Hukum, 2010)
ABSTRACT: Protection against forest ecosystem conservation in Aceh Tamiang manggrove decreased. This can be seen from the policy of land conversion in the forest ecosystem manggrove. Local governments have issued policies on the conversion of mangrove forest ecosystems that are not in accordance with its provisions, the conversion of the ecosystem of the mangrove forest to plantations. In addition, the exploitation of the mangrove forest by the community to the needs of charcoal that has lasted a long time and generations as well as land clearing for aquaculture ponds also cause damage to mangrove ecosystems. The conversion of mangrove forests has led to the effect that should be shouldered by the public, which reduced the catch of fishermen, the pollution of mangrove forest ecosystems.  The Convertion of Mangrove Forest Ecosystem  in Aceh Tamiang District